The Impact of Student-Teacher Relationships toward English-Speaking Performance - Nurfadhilah, Annisa; Jaya, Hariswan Putera (ENGLISH FRANCA : Academic Journal of English Language and Education, 2025)
This study investigated how student–teacher relationships relate to English-speaking performance among 154 second-year students at MAN 1 Ogan Ilir. Relationship quality was measured using the 25-item Student–Teacher Relationship Measure (S-TRM) and categorized into Good, Fair, and Poor groups. Speaking performance was assessed through a task on “My Favorite Hobby” using a rubric covering fluency, pronunciation, vocabulary, grammar accuracy, and comprehension, with 33 students (11 per group) evaluated. The results showed a moderate, significant correlation between relationship quality and speaking scores (r = 0.450, p = 0.009). ANOVA confirmed significant differences among the groups (F = 5.180, p = 0.012), with the widest gap between the Good and Poor groups. These findings highlight that positive student–teacher relationships contribute to stronger speaking performance, consistent with Vygotsky’s sociocultural view of learning.